Impact of Fair Value Measurement and Disclosure of Biological Assets Based on PSAK 69 on Agricultural Firm Value (2018-2022) - Fidelys Grecia Hutabarat; Retno Yuni Nur Susilowati; Liza Alvia; Widya Rizky Eka Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The agricultural sector plays an important role in Indonesia's capital markets, making a significant contribution to the economy despite facing the challenges of the COVID-19 pandemic. The consistent growth of this sector, marked by an increase in contribution to GDP by 2.20% in 2020 and 12.4% in 2022, has attracted investor interest. To support better investment decisions, agricultural companies need to improve the quality of the financial information they present. The implementation of PSAK 69, which requires disclosure of the fair value of biological assets, is an important step in increasing corporate transparency and accountability. This research aims to empirically test the influence of the fair value of biological assets and disclosure of biological assets on firm value in the Indonesian agricultural sector for the 2018-2022 period. The research was conducted using multiple linear regression analysis. The research results show that disclosure of biological assets has a positive effect on increasing firm value, while the fair value of biological assets does not have a significant effect.